2012
DOI: 10.1210/en.2012-1272
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Treatment Improves Hypothalamic Insulin and Leptin Signaling and Action and Reduces Obesity in Mice

Abstract: Topiramate (TPM) treatment has been shown to reduce adiposity in humans and rodents. The reduction in adiposity is related to decreased food intake and increased energy expenditure. However, the molecular mechanisms through which TPM induces weight loss are contradictory and remain to be clarified. Whether TPM treatment alters hypothalamic insulin, or leptin signaling and action, is not well established. Thus, we investigate herein whether short-term TPM treatment alters energy balance by affecting insulin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…First, topiramate can have effects on body weight; however, these are usually manifested only when topiramate is given in combination with phentermine and to animals who are obese or on high-fat diets (Liang et al, 2005;Caricilli et al, 2012). In the study reported here, topiramate had no effect on the weight of the animals in either the control or the STZ-treated group.…”
Section: Discussionmentioning
confidence: 65%
“…First, topiramate can have effects on body weight; however, these are usually manifested only when topiramate is given in combination with phentermine and to animals who are obese or on high-fat diets (Liang et al, 2005;Caricilli et al, 2012). In the study reported here, topiramate had no effect on the weight of the animals in either the control or the STZ-treated group.…”
Section: Discussionmentioning
confidence: 65%
“…After the recovery period of ten to 14 days, the icv location of the cannula was confirmed by drinking response after angiotensin II injection [57]. Mice with indwelling lateral cerebroventricular (LCV) cannula were fasted 22–24 hours and injected icv with insulin (4.4 mU/2μl) [58,59], leptin (4 μg/2μl) or saline (2μl). After 30 minutes, the mice were sacrificed and the MBH were dissected out, frozen in liquid nitrogen and kept at −80°Cuntil processed for protein extraction to measure PDE3B activity and p-AKT and p-STAT3 levels as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Recently proposed mechanism suggests that insulin suppresses PHLPP1 to enhance AKT activation but as lower insulin effectiveness prevails in aged hearts, it fails to decrease PHLPP1 during myocardial infarction/reperfusion, subsequently limiting AKT activity and cardioprotection (Xing et al 2016). One of the studies in obese mice confirmed that increased PHLPP1 expression allows pronounced AKT/PHLPP1 interaction which weakens the insulin response (Caricilli et al 2012) and hypothalamic silencing of PHLPP1 lead to greater weight loss and reduction in adiposity with improved insulin signaling in obese mice (Caricilli et al 2012). Altogether, the findings indicate that PHLPP1 isoform plays an important role in insulin signaling, therefore, specific therapies that inhibit this isoform in diabetes may be particularly useful; however, a firm demonstration is required to clarify the substrate selectivity of PHLPP isoforms in the diabetic paradigm.…”
Section: :3mentioning
confidence: 99%